1996
DOI: 10.1002/art.1780391011
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of synovial cells on EDA‐containing fibronectin

Abstract: Objective. To investigate the role of EDAcontaining fibronectin (EDA+ FN), a splice variant of FN detectable in association with cellular transformation, in the adherence of synovial cells (SC) on rheumatoid cartilage surface.Methods. migration, wound healing, and oncogenic transformation (1). FN is mainly composed of 2 subunits of protein that each have a molecular weight of -250 kd and are connected by disulfide bonds near the carboxyl terminus (2) (Figure 1). Multiple isoforms of FN are produced from a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…33) Our present result, showing that ACC-FN is more potent than pFN for adhesion of ACC3 cells, is consistent with these data. On the other hand, the immunohistochemical findings suggested that ED-B(+) FNs are associated with angiogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…33) Our present result, showing that ACC-FN is more potent than pFN for adhesion of ACC3 cells, is consistent with these data. On the other hand, the immunohistochemical findings suggested that ED-B(+) FNs are associated with angiogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, 1 mg/ml heparin inhibited by 35% the adherence of cultured synovial cells onto plasma-fibronectin-coated substratum [Hino et al, 1996]. Co-coating of plastic surface with 10 mg/ml plasma-fibronectin and 0.1-5 mg/ml heparin resulted in significant inhibition in the adherence of rat smooth muscle cells, the occurrence of which was maximal at 1 mg/ml heparin [Lundmark et al, 2001].…”
Section: Discussionmentioning
confidence: 96%
“…Inclusion of the alternatively spliced A domain is known to augment fibronectin's adhesion to integrin and its cell binding and spreading activity (20,35). The increased activity was not due to the binding of A to cells.…”
Section: Discussionmentioning
confidence: 99%